Two Oxidovanadium(V) Complexes with Hydrazone Ligands: Synthesis, Crystal Structures and Catalytic Oxidation Property - Yan Lei (Acta Chimica Slovenica, 2022)
Two new oxidovanadium(V) complexes, [VOL1(aha)]DMF (1) and [VOL2(mat)] (2), where L1 and L2 are the dianionic form of N'-(4-bromo-2-hydroxybenzylidene)-3-methyl-4-nitrobenzohydrazide and N'-(3,5-dibromo-2-hydroxybenzylidene)pivalohydrazide, respectively, and aha and mat are the monoanionic form of acetohydroxamic acid and maltol, respectively, have been synthesized and structurally characterized by physico-chemical methods and single crystal X-ray determination. X-ray analysis indicates that the V atoms in the complexes are in octahedral coordination. Crystal structures of the complexes are stabilized by hydrogen bonds. The catalytic property for epoxidation of styrene by the complexes was evaluated.